2017
DOI: 10.1002/jts.22223
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between PTSD and Functional Outcome Is Mediated by Perception of Cognitive Problems Rather Than Objective Neuropsychological Test Performance

Abstract: Posttraumatic stress disorder (PTSD) has been consistently linked to poorer functional outcomes, including quality of life, health problems, and social and occupational functioning. Less is known about the potential mechanisms by which PTSD leads to poorer functional outcomes. We hypothesized that neurocognitive functioning and perception of cognitive problems would both mediate the relationship between PTSD diagnosis and functioning. In a sample of 140 veterans of the recent wars and conflicts in Iraq and Afg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 71 publications
1
22
1
Order By: Relevance
“…This discrepancy in self‐report and objective functioning has been observed in samples with pain (Maor, Olmer, & Mozes, ; Middleton, Denney, Lynch, & Parmenter, ; Schmand et al, ; Schnurr & MacDonald, ) and PTSD (Binder, Storzbach, Anger, Campbell, & Rohlman, ; Samuelson, Abadjian et al, ; Mattson, Nelson, Sponheim, & Disner, ). Moreover, subjective impairment, but not objective performance, predicted functional outcomes (Hart et al, ; Samuelson, Bartel, Valadez, & Jordan, ; Samuelson, Abadjian et al, ; Spencer, Drag, Walker, & Bieliauskas, ). A recent study showed that the link between objective and subjective cognition was mediated by PTSD severity, further indicating that underlying this discrepancy is distress and appraisals (Mattson et al, ).…”
Section: Posttraumatic Stress Disordermentioning
confidence: 88%
See 1 more Smart Citation
“…This discrepancy in self‐report and objective functioning has been observed in samples with pain (Maor, Olmer, & Mozes, ; Middleton, Denney, Lynch, & Parmenter, ; Schmand et al, ; Schnurr & MacDonald, ) and PTSD (Binder, Storzbach, Anger, Campbell, & Rohlman, ; Samuelson, Abadjian et al, ; Mattson, Nelson, Sponheim, & Disner, ). Moreover, subjective impairment, but not objective performance, predicted functional outcomes (Hart et al, ; Samuelson, Bartel, Valadez, & Jordan, ; Samuelson, Abadjian et al, ; Spencer, Drag, Walker, & Bieliauskas, ). A recent study showed that the link between objective and subjective cognition was mediated by PTSD severity, further indicating that underlying this discrepancy is distress and appraisals (Mattson et al, ).…”
Section: Posttraumatic Stress Disordermentioning
confidence: 88%
“…Complaints of cognitive problems have been frequently described in both pain sufferers and trauma‐exposed individuals, yet the mechanisms driving these negative and discrepant self‐report responses were unclear. Previous studies have found that objective cognitive performance is not always related to subjective cognitive performance (Binder et al, ; Maor et al, ; Middleton et al, ; Samuelson, Abadjian et al, ; Schmand et al, ; Schnurr & MacDonald, ; Mattson et al, ), and that subjective, rather than objective, cognitive performance predicts psychosocial functioning in patients with PTSD (Samuelson, Abadjian et al, ). In our samples, there remained a large direct effect of PTSD on perceived cognitive functioning, suggesting that appraisals may be partially driven by an accurate, likely objective change in cognitive functioning, as well as by accompanying somatic burden.…”
Section: Discussionmentioning
confidence: 98%
“…While many studies linking PTSD and/or depression to cognitive decline or dementia have been performed in older populations [ 11 , 12 , 41 , 42 , 43 ], there is some evidence of an association between these mental health conditions and cognition in younger age groups as well [ 8 , 9 , 10 , 13 , 45 ]; for example, PTSD and depression were associated with worse cognitive outcomes in middle-aged military veterans [ 8 , 9 ] and general populations [ 13 , 45 ]. Additionally, investigations that assessed self-perception of cognitive functioning in young and middle-aged veterans have similarly found associations between PTSD symptoms and/or depressive symptoms and self-perceived cognitive impairment, despite using different subjective cognitive measures than the current study—i.e., the Neurobehavioral Symptom Inventory and the Everyday Memory Scale [ 17 , 18 ]. Because PTSD symptoms and depressive symptoms were assessed at the same time point as subjective cognitive concerns in the current study, further investigation of the pathways between these mental health conditions and cognition will be needed in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with PTSD showed deficits in several neurocognitive domains including attention, learning, and processing speed [ 14 , 15 ]. While the above analyses involved objective cognitive assessments, the literature contains evidence that PTSD symptoms and depressive symptoms are associated with greater subjective cognitive concerns as well [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses reveal significant differences between individuals with PTSD compared to healthy and trauma-exposed controls, representing medium to large effect sizes, in the domains of verbal learning and memory, processing speed, attention/working memory, and executive functions (12,13). Moreover, patients with PTSD self-report cognitive problems with detrimental impacts on social and occupational functioning (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%